Estimated state and local fiscal effects of the Nurse Family Partnership program - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2009)
This short paper estimates the state and local fiscal benefits of the Nurse Family Partnership (NFP) program. NFP provides nurse home visiting services to low-income first-time mothers. In addition to social benefits, NFP provides state and local fiscal benefits by reducing costs of social services, welfare, and crime, and increasing tax receipts due to increased earnings of mothers and former child participants when they grow up. Based on previous studies, this paper estimates that the present value, in 2007 dollars, of these state and local fiscal benefits is a little over 15,000 per NFP case.
Keywords: H75; H71; I18; J48; 330